Ekspresi Romantik dalam Puisi Asyiq min Falishtin Karya Mahmud Darwish (Analisis Aliran Romantisme) - Noor, Muhammad Arsyad; Effendi, Irfan; Rasyid, Ahsan (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
The poem Asyiq min Falishtin is a poem with a romantic flow. This poem contains expressions of Mahmud Dharwis' feelings of longing for the peace and prosperity of Palestine, as well as describing the sadness and suffering suffered by the land of Palestine, so this poem is synonymous with expressions of feelings expressed in the form of expressions. This research is to analyze aspects of romantic expression in this poetry, which does not only focus on romance but the expression of feelings. By using descriptive qualitative research methods, it can be seen that Asyiq min Falisthin's poetry is poetry with a romantic flow, this is proven by the presence of romantic elements, namely the content of the poem tells about me who was hit by longing for the country of Palestine, using words that go back to nature, by calling herself "I" shows individualism, telling about how much the author longs and loves her and the suffering of the people of her country due to colonialism, shows primivism, uses elements of sentimentalism by expressing excessive emotions of sadness and depicting life as if it were strange.